Model Renumerasi Staf Medis Spesialis di RSUP Sanglah - Tri Virgo Wati (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTRemuneration / compensation is a means to motivate the performance of human resources to achieve organizational goals. Medical staff specialists as government employees and JKN implementations implementing the INA CBG system for payment of patient claims, provide a challenge in determining remuneration models for medical specialist staff at Sanglah Hospital. To find remuneration models of medical specialist staff that can be implemented, this study uses qualitative design, with in-depth interviews of informants from management staff as policy makers and specialist medical staff as users. There are two components of remuneration that are expected to meet eligibility and fairness in remuneration of medical specialist staff who assess the position and reward for performance. Awards for medical staff specialist positions using FES (Factor Evaluation System). Factors of work experience based on length of service should be added as consideration in the assessment of medical staff specialist positions. The rewards for performance are differentiated into rewards for quantity, quality, and work behavior. The performance of quantity awards is determined by using the activity as an indicator by considering the weight between activities and between groups of specialized medical staff. Quality and behavioral assessments use measurable and applicable indicators both established by the organization and government